Argumentation Study of College Students Who Are Smokers - Setiyo Prajoko (Universitas Tidar, 2020)
This study aims to examine the arguments of college students who are smokers at Universitas Tidar (Tidar University). The research method used in this study is a survey method with two instruments which are interview and questionnaire conducted in December 2019. The data is analyzed by using descriptive qualitative method. The respondents in this study are 15 college students from some faculties in Universitas Tidar. Based on the result of interview and questionnaire, it shows that in the campus environment, there are some students who know the rules about the prohibition of smoking in the campus environment especially Universitas Tidar. In fact, a research about the argumentation study of college students who are smokers shows that there are still some students who smoke in the campus environment. Moreover, 67% of the college students are not ashamed when the lecturers see them smoking. In addition, the results obtained as much as 100% of respondents know about the negative effects of smoking. However, there are only 67% of respondents who just have the desire to stop smoking and it even has not been realized. They are still smoking with the reason that they still feel the advantages or positive effects of smoking for them. As the example, smoking can increase their morale and reduce stress. They also have not felt the negative effects on their health conditions such as breathless and current finances.